Influence Of Egg Shape And Egg Weight On Characteristic Of Quilted Egg (Coturnix Coturnix Japonica) - Rozi, Ahmad Fahrul; Sudrajat, Deden; Anggraeni, Anggraeni (Universitas Djuanda Bogor, 2018)
Research on Influence of Egg Shape and Egg Weight on Characteristic ofÂ Quilted Egg (Coturnix coturnix japonica) has been done for one month, this research aim to know the influence of egg shape and egg weight to fertility, hatchability,Â hatching weight, and sex in bird Quail and can select good egg weight to hatch. This study used quail eggs (Coturnix coturnix japonica), as many as 216 grains divided into two groups. Each is a group with an egg shape (pointed, semi-pointed, and round) and group with egg weight (mild, moderate, and severe). The hatching machine used is semi-automatic hatching machine, before the egg is inserted into the hatching machine is done selection that includes egg shape and egg weight, egg shape selection is done by measuring the width and length of eggs using sliding and egg weight is done by weighing the eggs with scales digital. The first factor is egg form with three levels, A1 (egg taper = 75 - 78,12%), A2 (semi-pointed egg = 79,59 - 82,11%), and A3 (round = 82,78 - 86,76 %). While the second factor is the egg weight of three levels namely B1 (light weight = 9 - 10 grams), B2 (Medium weight = 11-12 grams) and B3 (Weight = 13-14 grams). Of the 2 factors with three levels were obtained 9 treatment combinations of each treatment repeated 4 times, each repetition consisted of 6 grains. The experimental design used was Completely Randomized Design (RAL) 3 x 3 factorial pattern for fertility variables, hatchability, hatching weight and percentage of male sex. The results showed that the eggs did not give a significant effect on fertility, hatchability, hatching and sex weights, whereas for egg weight only had a significant effect on hatch and percentage of male sex.